Pharmacokinetics of (-)-(S)-Bromofosfamide after Intravenous and Oral Administration in Mice - Kobylińska, Kamila; Kobylińska, Maria; Sobik, Barbara (Arzneimittelforschung, 2001)
(-)-(S)-Bromofosfamide ((2S)-(2-chloro-ethylamino)-3-(2-bromoethyl)-1,3,2-oxa-zaphosphorinane 2-oxide, CAS 146452-37-1, CBM-11) is a new potential anticancer drug, currently under investigation. Its pharmacokinetics and bioavailability were studied in female mice following intravenous and oral administration of the dose of 50 mg/kg. The compound was extracted from plasma samples using chloroform and analyzed by high-performance liquid chromatography with UV detection at 200 nm. Orally administered (-)-(S)-bromo-fosfamide was absorbed quickly, attaining a maximum level of 33.9 μg/ml at 5 min, and was eliminated with a half-life (t1/2) of about 0.9 h. The average half-life of intravenously administered (-)-(S)-bromofosfamide was about 0.7 h. The total plasma clearance (CL) and volume of distribution (Vd) were found to be 0.14 l/h and 4.92 l/kg, respectively. The absolute bioavailability of (-)-(S)-bromofosfamide after oral administration was 105 %.
Keywords: Bromofosfamide, biovailabil-ity, mouse, pharmacokinetics; CAS 146452-37-1; CBM-11; Cytostatics; Ifosfamide analogues